Opinion mining method on hot topic of micro−blog - Guang-lei ZHANG; Ya-bin XU (Tongxin xuebao)
A method of opinion mining was argued in connection with hot topic of micro-blog.Firstly,opinion sentences are identified by syntactic dependencies templates and support vector machine (SVM).Secondly,the opinion words can be get in opinion sentences by syntactic dependencies and lexical relations,thus they can be displayed clearly.Finally,the experiment proves the effectiveness of this method.